CONCEPTUAL APPROACHES TO THE DEFINITION OF THE CONCEPT OF «VIRTUAL ASSETS» IN UKRAINE AND AROUND THE WORLD - Ushynkina, Oleksandra (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: study of global approaches to the definition of the concept of «virtual assets» in order to further distinguish and borrow the most relevant definitions into Ukrainian legislation. Research methods: in the course of the work, general scientific and special scientific methods of cognition were used, including: methods of analysis and synthesis, which were used to research the legislation of different countries; the comparative legal method, which is used when comparing legal norms of the same name; the historical-legal method, with the help of which the step-by-step development of approaches to the definition of the concept of «virtual assets» in regulatory and legal acts was investigated. Results: global approaches to defining the content of the concept of virtual assets are outlined; the main trends in the context of defining the concept of «virtual assets» are defined and formulated. Discussion: the study of foreign approaches to the legal definition of virtual assets and their classification is essential for the development of domestic legislation, which only partially corresponds to current trends. Such trends are the use of the term «virtual asset» instead of the term «virtual currency»; application of a reference to distributed ledger technology or similar technology in the definition of the concept of «virtual asset»; implementation of the classification of virtual assets at the legislative level according to the functional criterion. Ukrainian legislation in the field of regulation of virtual assets in terms of the definition and types of virtual assets does not correspond to current foreign approaches, as the legislator does not take into account a number of important aspects that relate to the essence of virtual assets. A limited legislative approach can create a situation where the majority of virtual assets will remain outside the legal field of the state.